(untitled) (Bangladesh Journal of Medical Science, 2020)
Objectives: The present study was designed to screen the antibacterial and synergistic effects of Allium sativum, Ecballiumelaterium, Pelargoniumgraveolens, Rosmarinusofficinalis, Phagnalonrupestre and Rutagraveolens plant extracts and essential oils against the followingclinical multidrug-resistant(MDR) Gram negative pathogenic isolates: Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa. Methods: All extracts and essential oils were screened for their antibacterial activity and synergistic effect in combination with known antibiotics.The minimum inhibitory concentrations (MICs) and the minimum bactericidal concentrations (MBCs) of the plant extracts were assessed. Results: Our results revealed that, the average diameter of inhibition zones ranged from: 7-14 mm, 7-17 mm, 8-17 mm and 7-13 mm for water, ethanol, methanol and EOs extracts, respectively. The MICs and MBCs were determined for extracts which showed antibacterial activity. The average MICs values ranged from 1.6-100 mg/ml, 1.6-50 mg/ml, 0.39 -50 mg/ml and 3.13-100 μl/ml for water, ethanol, methanol and EOs extracts, respectively. While MBCs values ranged from 25->200 mg/ml, 25- 200 mg/ml and 50->200 μl/ml for water, ethanol, methanol and EOs extracts, respectively. The antibacterial activity of the afore mentioned plant extracts combined with Ciprofloxacin (CIP), Ampicillin (AM), Cefotaxime (CTX), Nalidixic acid (NA), Norofloxacin (NOR), Cefuroxime (CXM), Cefaclor (CF), Ofloxacin (OFX), Cefalexin (CL), Tetracycline (TE), Rifampicin (RIF), Amoxyclav (AMC) and Amikacin (AK) had different degrees of synergism against the selectedbacteria.Essential oils (Eos) of screened plants had the best synergism with antibiotics than the plant extracts against the tested bacteria. The best synergism was noticed in the Eos of A. sativum, P. graveolens and R. officinalis. Conclusion: It was concluded that the synergistic effect of antibiotics and plant extracts is promising approach fortreating infectious diseases caused byMDR Gram negative bacteria. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.509-519